(Un)papering the cracks in South Africa : the role of 'traditional' and 'new' media in nation-negotiation around Julius Malema on the eve of the 2010 FIF World Cup - Rodrigues, Erika (Social Anthropology, 2015)
In April 2010, amidst the nation-unifying discourses prevalent during the preparation for the 2010 FIFA Soccer World Cup™ to be hosted in South Africa, a series of events gave rise to the revitalization of other discourses in the national media: those of racial polarization and the possibility of a race war.